MODIFIKASI ALAT PENYEMBELIH SAPI SEDERHANA SISTEM KANDANG JEPIT - Budriyadi, Syefi; Lestari, Dwi Mardika; Mardiyana, Dani (Universitas Nusa Putra, 2022)
The process of slaughtering cattle at Slaughterhouses (RPH) usually uses a Killing Box which functions as a place for slaughter by clamping and laying the cows down so that handling during slaughter is easier. However, this tool is still quite expensive, so not all abattoirs use this tool in the slaughtering process. The traditional way is still widely used, namely by pulling/slamming the cow's body so that it is helpless. The cattle slaughtering tool with the clamp cage system that has ever been made is quite helpful and makes it easier to slaughter animals. However, there are still some drawbacks to this tool, including the alternating wires that have broken, the wheels are damaged quickly, and the lack of bottom supports. Therefore, it is necessary to modify this cattle slaughtering tool so that no more problems occur. In this research, modifications are limited to the frame, alternating wire and wheels. The method used in this research is analytical calculation method. The results showed that the fixed frame and movable frame materials did not need to be replaced because the maximum stress received by each frame was still below the allowable stress, while the alternating wires had to be replaced with wires with a minimum diameter of 8 mm. bottom support that can withstand a load of 225 kg/pc